2011
DOI: 10.1126/science.1201889
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Decreases Food Intake Through Activation of POMC Neurons

Abstract: Smoking decreases appetite and smokers often report that they smoke to control their weight. Understanding the neurobiological mechanisms underlying the anorexic effects of smoking would facilitate the development of novel treatments to help with smoking cessation and to prevent or treat obesity. Using a combination of pharmacological, molecular genetic, electrophysiological and feeding studies, we found that activation of hypothalamic α3β4 nicotinic acetylcholine receptors (nAChRs) leads to activation of pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
298
7
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 353 publications
(343 citation statements)
references
References 33 publications
22
298
7
9
Order By: Relevance
“…Beyond nicotine anorectic action, nAChRs are well known to be involved in the regulation of food intake. In the lateral hypothalamus, neuronal networks express α4β2 and α7nAChRs [27][28][29] whereas α3β4 nAChRs seem rather implicated in both stimulation of POMC neurons [30] and inactivation of hypothalamic AMPK [31]. Surprisingly, the slight hyperphagia of α7β2nAChR −/− mice did not change their body weight but was associated with a modification of their body composition, with increased lean and bone mass and decreased fat pads, which can explain their increased sensitivity to fasting-induced weight loss.…”
Section: Discussionmentioning
confidence: 97%
“…Beyond nicotine anorectic action, nAChRs are well known to be involved in the regulation of food intake. In the lateral hypothalamus, neuronal networks express α4β2 and α7nAChRs [27][28][29] whereas α3β4 nAChRs seem rather implicated in both stimulation of POMC neurons [30] and inactivation of hypothalamic AMPK [31]. Surprisingly, the slight hyperphagia of α7β2nAChR −/− mice did not change their body weight but was associated with a modification of their body composition, with increased lean and bone mass and decreased fat pads, which can explain their increased sensitivity to fasting-induced weight loss.…”
Section: Discussionmentioning
confidence: 97%
“…Studies suggest that nicotine promotes increased energy expenditure and reduces appetite, which explains why smokers having a lower BMI than nonsmokers, and the common weight gain after smoking cessation 12,31,32 . In contrast, it is observed that heavy smokers (> 40 cigarettes/day) tend to have higher body weight than light smokers (< 20 cigarettes/day).…”
Section: Discussionmentioning
confidence: 99%
“…NPY dan orexin dapat meningkatkan nafsu makan. 27 Nikotin ikut terhirup pada saat seseorang merokok atau terpapar asap rokok.…”
Section: Pembahasanunclassified